Metabolic dysfunction-associated steatotic liver disease as a predictor of cognitive performance: An 11-year population-based follow-up study - Vataja, Emilia; Viitanen, Matti; Rinne, Juha O; Lehtisalo, Jenni; Erlund, Iris; Ngandu, Tiia; Koskinen, Seppo; Åberg, Fredrik; Jula, Antti; Ekblad, Laura (Elsevier BV, 2025)
Background: Prevalent manifestation of metabolic dysfunction, metabolic dysfunction-associated steatotic liver disease (MASLD), has been associated with poorer cognitive performance and greater decline in cognitive functions.
Aim: The aim of this study was to analyze whether MASLD, measured by fatty-liver-index (FLI), predicts decline in cognitive performance during 11 years.
Methods: This study was based on the Finnish nationwide, population-based Health 2000 Health Examination Survey and its follow-up, Health 2011 Survey. Cognitive performance was assessed with verbal fluency, word-list learning (WLL), delayed word-list recall (both at baseline and at follow-up), and with simple reaction time and visual choice reaction time tests (only at baseline). Statistical analyses were performed using multivariate linear regression adjusted for age, sex, education, APOE ε4 genotype, hypercholesterolemia, diabetes mellitus, hypertension, depressive symptoms, physical activity smoking status, C-reactive protein and HOMA of insulin resistance.
Results: Cross-sectionally, 5,139 (mean age 52.3 years) and longitudinally, 3,143 (mean age 49.3 years) participants were examined. Cross-sectionally, no associations between FLI and cognitive performance were found in the adjusted models. Longitudinally, baseline FLI > 60 predicted poorer WLL (p < 0.005) and a decline in WLL from baseline to follow-up (p < 0.04).
Conclusions: Our results suggest that MASLD is an independent predictor of decline in a test measuring working memory and learning.